Impact of Latency Variations on the Predictive Value of Facial Nerve Proximal-to-Distal Amplitude Ratio during Vestibular Schwannoma Surgery - Ashram, Yasmine A.; Zohdy, Youssef M.; Garzon-Muvdi, Tomas (Journal of Neurological Surgery Part B: Skull Base, 2023)
Introduction This study highlights the relation between compound muscle action potential (CMAP) latency variations and the predictive value of facial nerve (FN) proximal-to-distal (P/D) amplitude ratio measured at the end of vestibular schwannoma resection.Methods Forty-eight patients underwent FN stimulation at the brainstem (proximal) and internal acoustic meatus (distal) using a current intensity of 2 mA. The proximal latency and the P/D amplitude ratio were assessed. House–Brackmann grades I & II indicated good FN function, and grades III to VI were considered fair/poor function. A P/D amplitude ratio > 0.6 was used as a cutoff to indicate a good FN function, while a ratio of ≤ 0.6 indicated a fair/poor FN function.Results The P/D amplitude ratio was measured for all patients, and the calculated sensitivity (SE), specificity (SP), positive predictive value (PPV), and negative predictive value (NPV) were 85.2, 85.7, 88.5, and 81.8%, respectively. The CMAPs from the mentalis muscle were then classified based on their proximal latency into group I (< 6 ms), group II (6–8 ms), and group III (> 8 ms). The SE, SP, PPV, and NPV became 90.5, 90.9, 95, and 83.3%, respectively, in group II. In group I, SE and NPV increased, whereas SP and PPV decreased. While in group III, SP and PPV increased, whereas SE and NPV decreased.Conclusion At a latency between 6 and 8 ms, the P/D amplitude ratio was predictive of outcomes with high SE and SP. When latency was < 6 ms or > 8 ms, the same predictive ability was not observed. Knowing the strengths and limitations is important for understanding the predictive value of the P/D amplitude ratio.
Keywords: facial nerve; intraoperative monitoring; triggered EMG; vestibular schwannoma; latency; proximal to distal amplitude ratio; postoperative outcome; predictive value